The cellular composition of the tumor microenvironment is an important marker for predicting therapeutic efficacy in breast cancer - Dou, Tingyao; Li, Jing; Zhang, Yaochen; Pei, Wanru; Zhang, Binyue; Wang, Bin; Wang, Yanhong; Jia, Hongyan (Frontiers in Immunology, 2024)
At present, the incidence rate of breast cancer ranks first among new-onset malignant tumors in women. The tumor microenvironment is a hot topic in tumor research. There are abundant cells in the tumor microenvironment that play a protumor or antitumor role in breast cancer. During the treatment of breast cancer, different cells have different influences on the therapeutic response. And after treatment, the cellular composition in the tumor microenvironment will change too. In this review, we summarize the interactions between different cell compositions (such as immune cells, fibroblasts, endothelial cells, and adipocytes) in the tumor microenvironment and the treatment mechanism of breast cancer. We believe that detecting the cellular composition of the tumor microenvironment is able to predict the therapeutic efficacy of treatments for breast cancer and benefit to combination administration of breast cancer.